Evolution of the Greater Caucasus Basement and Formation of the Main Caucasus Thrust, Georgia. Issue 3 (21st March 2020) - Vasey, Dylan A.; Cowgill, Eric; Roeske, Sarah M.; Niemi, Nathan A.; Godoladze, Tea; Skhirtladze, Irakli; Gogoladze, Salome
Abstract: Along the northern margin of the Arabia‐Eurasia collision zone in the western Greater Caucasus, the Main Caucasus Thrust (MCT) juxtaposes Paleozoic crystalline basement to the north against Mesozoic metasedimentary and volcaniclastic rocks to the south. The MCT is commonly assumed to be the trace of an active plate‐boundary scale structure that accommodates Arabia‐Eurasia convergence, but field data supporting this interpretation are equivocal. Here we investigate the deformation history of the rocks juxtaposed across the MCT in Georgia using field observations, microstructural analysis, U‐Pb and 40 Ar/ 39 Ar geochronology, and 40 Ar/ 39 Ar and (U‐Th)/He thermochronology. Zircon U‐Pb analyses show that Greater Caucasus crystalline rocks formed in the Early Paleozoic on the margin of Gondwana. Low‐pressure/temperature amphibolite‐facies metamorphism of these metasedimentary rocks and associated plutonism likely took place during Carboniferous accretion onto the Laurussian margin, as indicated by igneous and metamorphic zircon U‐Pb ages of ~330–310 Ma. 40 Ar/ 39 Ar ages of ~190–135 Ma from muscovite in a greenschist‐facies shear zone indicate that the MCT likely developed during Mesozoic inversion and/or rifting of the Caucasus Basin. A Mesozoic 40 Ar/ 39 Ar biotite age with release spectra indicating partial resetting and Cenozoic (<40 Ma) apatite and zircon (U‐Th)/He ages imply at least ~5–8 km of Greater Caucasus basement exhumation since ~10 Ma in response to Arabia‐Eurasia collision. Cenozoic reactivation of the MCT may have accommodated a fraction of this exhumation. However, Cenozoic zircon (U‐Th)/He ages in both the hanging wall and footwall of the MCT require partitioning a substantial component of this deformation onto structures to the south. Plain Language Summary: Collisions between continents cause deformation of the Earth's crust and the uplift of large mountain ranges like the Himalayas. Large faults often form to accommodate this deformation and may help bring rocks once buried at great depths up to the surface of the Earth. The Greater Caucasus Mountains form the northernmost part of a zone of deformation due to the ongoing collision between the Arabian and Eurasian continents. The Main Caucasus Thrust (MCT) is a fault juxtaposing old igneous and metamorphic (crystalline) rocks against younger rocks that has often been assumed to be a major means of accommodating Arabia‐Eurasia collision. This study examines the history of rocks along the MCT with a combination of field work, study of microscopic deformation in rocks, and dating of rock formation and cooling. The crystalline rocks were added to the margins of present‐day Eurasia about 330–310 million years ago, and the MCT first formed about 190–135 million years ago. The MCT is likely at most one of many structures accommodating present‐day Arabia‐Eurasia collision. Key Points: Amphibolite‐facies metamorphism and plutonism in the Greater Caucasus basement took place ~330–310 Ma The Main Caucasus Thrust formed as a greenschist‐facies shear zone during Caucasus Basin inversion and/or rifting (~190–135 Ma) The Main Caucasus Thrust may have helped facilitate a portion of at least 5–8 km of basement exhumation during Arabia‐Eurasia collision